2007
DOI: 10.1590/s0034-89102006005000049
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos a antibióticos em pacientes internados em um hospital universitário

Abstract: Adverse events to antibiotics in inpatients of a university hospital ABSTRACTOBJECTIVE: Antibiotics are the most common drugs causing adverse events and they lead to problems to patients and additional costs of the health system. The aim of the study was to evaluate the occurrence of adverse events to antibiotics in inpatients of a hospital. METHODS:An extensive drug monitoring was conducted in adult inpatients taking antibiotics in the city of Maringá, Southern Brazil, from September 2002 to February 2003. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 14 publications
1
4
0
12
Order By: Relevance
“…In this study, few prescriptions analyzed contained the correct and complete specifications, which are paramount for treatment success. These Table 2 Distribution of drug prescriptions in terms of changes made, date and timing, from December 2002 to January 2003. findings corroborate other previous studies and demonstrate the need to restructure the medication process to avoid omission of information in prescriptions 30,31 . The literature affirms that most hospitals do not have a computerized physician order entry system yet, and for this reason the incorporation of the pharmacist into the health care team is a more feasible alternative to checking prescription completeness to avoid these errors 14,30,31 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, few prescriptions analyzed contained the correct and complete specifications, which are paramount for treatment success. These Table 2 Distribution of drug prescriptions in terms of changes made, date and timing, from December 2002 to January 2003. findings corroborate other previous studies and demonstrate the need to restructure the medication process to avoid omission of information in prescriptions 30,31 . The literature affirms that most hospitals do not have a computerized physician order entry system yet, and for this reason the incorporation of the pharmacist into the health care team is a more feasible alternative to checking prescription completeness to avoid these errors 14,30,31 .…”
Section: Discussionsupporting
confidence: 92%
“…The omission of this information may cause the interruption of drug administration before the foreseen treatment duration. In the case of antibiotics, for instance, the interruption before the foreseen treatment duration may cause bacterial resistance and the inability to use subsequently the same antimicrobial agent 30 .…”
Section: Changes and Types Hospitalsmentioning
confidence: 99%
“…4 In Brazil, studies on adverse events, which included errors in prescription, storage and administration, have already improved, being of special interest a study on intensive monitoring of antimicrobials in a Paraná hospital, which identified the occurrence of 91 adverse events, being 3.3% adverse reactions to medication and 7.7% medication errors. 5 Meanwhile, in a university hospital in Ribeirão Preto, SP, 925 prescriptions were analyzed, with 21.1% presenting text erasures, and 28.2% presenting unclear information to the professionals. In another study, 7 conducted in a reference public hospital in Minas Gerais, there was an analysis of 4026 prescriptions with items containing potentially dangerous medication, which found 89.1% of problems belonging to four categories: absence of dosage and phamaceutical form, poor readability and doubtful dosage.…”
Section: Introductionmentioning
confidence: 99%
“…2 A importância de problemas de decisão na prescrição foi observada em estudo sobre antibióticos realizado em hospital universitário brasileiro, tendo sido registrados 91 incidentes, dos quais 7,7% foram considerados erros de prescrição e de tipo de decisão. 16 Conforme Aspden et al 2 (2007), as recomendações com maior evidência científi ca para a prevenção de erros de medicação em hospitais são: adoção da prescrição eletrônica com o devido suporte clínico, inclusão de farmacêuticos nas visitas clínicas, viabilização de contato com farmacêuticos durante 24 horas para solucionar dúvidas em relação a medicamentos, e presença de procedimentos especiais e protocolos escritos para o uso de MPP. Esta última medida poderá prevenir parte considerável dos erros com medicamentos de alto risco.…”
unclassified